Is a spice missing from the recipe? The intra‐cellular localization of vanillin biosynthesis needs further investigations. (16th September 2022) - Diamond, A.; Barnabé, S.; Desgagné‐Penix, I.
Abstract: Vanillin is the most popular flavor compound in the world. Substantial effort were made in the last decades to completely elucidate the metabolic pathway that leads to vanillin in plants, with some controversy reported. In V. planifolia, vanillin biosynthesis occurs in plastids or in redifferentiated‐plastids termed ''phenyloplasts''. More recently, it was shown that all enzymes required for the conversion of [ 14 C]‐phenylalanine to [ 14 C]‐vanillin‐glucoside are confined within that organelle. However, knowing that some of these enzymes are cytosolic or ER‐membrane bound in most plant species, it raises questions on the interpretation of data obtained from the technique used and on the true localization of the biosynthetic enzymes in V.planifolia . In addition, intense debate has emerged about the real participation of last enzyme of the pathway involving vanillin synthase (VpVAN) in the direct conversion of ferulic acid to vanillin. With the discovery of another enzyme capable of this conversion and the lack of activity of VpVAN in vitro, further disagreement emerged. One additional challenge to VpVAN being necessary and sufficient is that the transcript for this protein is abundant invarious non‐vanillin‐producing tissues of the vanilla plant. In this viewpoint, we discuss the findings surrounding the cellular‐localization and activity of enzymes of vanillin biosynthesis. This will help to further understand the pathway and urge for additional research study to resolve the debate. Abstract : Is there a spice missing in the recipe? The intra‐cellular localization of vanillin biosynthesis needs more investigations.